Leuconostoc mesenteroides SJRP55: a bacteriocinogenic strain isolated from Brazilian water buffalo mozzarella cheese - Paula, Aline Teodoro de [UNESP]; Jeronymo-Ceneviva, Ana Beatriz [UNESP]; Silva, Luana Faria [UNESP]; Todorov, Svetoslav Dimitrov; Franco, Bernadette Dora Gombossy de Melo; Choiset, Yvan; Haertlé, Thomas; Chobert, Jean-Marc; Dousset, Xavier; Penna, Ana Lúcia Barretto [UNESP] (Springer Nature, 2014)
The production of bacteriocins by Leuconostoc mesenteroides represents an important opportunity for exploration of their potential use for industrial purpose. The antimicrobial compounds produced by L. mesenteroides subsp. mesenteroides SJRP55 strain were characterized and purified. Cell-free supernatant of Leuc. mesenteroides subsp. mesenteroides SJRP55 produced antibacterial compounds against Listeria spp. strains and not inhibiting against Lactobacillus spp. The antimicrobial substances were stable at high temperatures (100 C for 2 h and 121 C for 20 min) and low pH (pH 2–4) values, but sensitive to proteolytic enzymes and resistant to aamylase, lipase and catalase enzymes. The optimal temperature for active peptides production was 25 C. The antimicrobial compounds were purified by ammonium sulfate precipitation, affinity column and reverse-phase chromatography. Mass spectrometry and amino acids analyses showed that the bacteriocins were identical to mesentericin Y105 and B105. The producer strain’s DNA analysis revealed presence of open reading frames possibly coding for virulence factors, such as enterococcal surface protein (esp), collagen adhesion (ace) and intrinsic vancomycin resistance (vanA); however, biogenic amines encoding genes were not observed. Leuc. mesenteroides subsp. mesenteroides SJRP55 is a promising biopreservative culture in fermented milk, and the purified bacteriocins can also be applied in food preservation.
Keywords: Mesentericin Y105 and mesentericin B105; Leuconostoc mesenteroides subsp. mesenteroides; Antimicrobial activity; Purification; Lactic acid bacteria